ANALISIS STRATEGI PEMADANAN NIK MENJADI NPWP DALAM RANGKA MENINGKATKAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA BEKASI BARAT 2023 - Khamid, Azwar; Supriyono, Supriyono (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Through the Integration of NIK into NPWP policy, the Directorate General of Taxes has made a new breakthrough that will implement a Single Identification Number (SIN) between NIK and NPWP. The purpose of this research is to analyse the strategy of matching NIK to NPWP in order to increase individual taxpayer compliance at the West Bekasi Primary Tax Service Office in 2023. This research method uses a qualitative descriptive method. This research uses the theory of Azhari Aziz Samudra (Barlian, Rossya and Rulandari, 2021). The results of this study showed that the West Bekasi Primary Tax Office Strategy for the existence of the NIK to NPWP Policy has been able to increase the number and compliance of taxpayers through various media, as well as the characteristics of friendly and professional extension services. But there are still obstacles that affect the NIK to NPWP Matching strategy so that the matching process has not been fully achieved. Some strategies carried out on this policy are to improve the education process through socialisation and counseling by always utilising technological advances and various existing social media so that information about the NIK to NPWP policy can be disseminated evenly.Through the Integration of NIK into NPWP policy, the Directorate General of Taxes has made a new breakthrough that will implement a Single Identification Number (SIN) between NIK and NPWP. The purpose of this research is to analyse the strategy of matching NIK to NPWP in order to increase individual taxpayer compliance at the West Bekasi Primary Tax Service Office in 2023. This research method uses a qualitative descriptive method. This research uses the theory of Azhari Aziz Samudra (Barlian, Rossya and Rulandari, 2021). The results of this study showed that the West Bekasi Primary Tax Office Strategy for the existence of the NIK to NPWP Policy has been able to increase the number and compliance of taxpayers through various media, as well as the characteristics of friendly and professional extension services. But there are still obstacles that affect the NIK to NPWP Matching strategy so that the matching process has not been fully achieved. Some strategies carried out on this policy are to improve the education process through socialisation and counseling by always utilising technological advances and various existing social media so that information about the NIK to NPWP policy can be disseminated evenly.